Korespondensi Fonemis Bahasa Melayu Langkat dan Melayu Makasar - Diva Nitama Putri; Muhammad Suryadi; Mujid Farihul Amin (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2022)
The study aims to describe the phonemic correspondence formula from the Melayu Langkat and Melayu Makasar languages. The method in this study uses the language grouping method with phonemic correspondence techniques.  Melayu Langkat and Melayu Makasar language are languages derived from the same family, namely the Austronesian family. As result, the phonemic correspondence formula can be seen between the Melayu Langkat and Melayu Makasar languages showing regular phonemic forms of correspondence in the form of vowels and consonants. The phonemic correspondence formulas in Melayu Langkat and Melayu  Makasar languages obtained are: /n~ŋ/, /m~ŋ/, /i~e/, /o~u/, /e~a/, /t~?/, /t~k/, /Ť~Ď/, /e~ә/